CoolBot is promising technology for farmers - Dubey, Neeru; Raman, NagaLaxmi M (Indian Horticulture, 2019)
The CoolBot enables room maintains a temperature of temperature of 5-6 oC and shelf-life of cabbage (15 days), brinjal (10 days), tomato (20 days), green chilli (25 days), cauliflower (15 days), french beans (15 days), and coriander (12 days).